Influence of cobalt addition and calcination temperature on the physical properties of BaFe12O19 hexaferrites nanoparticles. (13th January 2020) - Rekaby, M; Shehabi, H; Awad, R
Abstract: Nano-scale particles of pure Barium hexaferrite 'BaFe12 O19 ' and Cobalt added Barium hexaferrite 'Cox BaFe12 O19 ', with x = 0.04, 0.06 and 0.1 wt%, were successfully synthesized by the chemical co-precipitation method. The synthesized powder was subjected to different calcination temperatures (T = 850 °C, 900 °C, 950 °C and 1050 °C). X-ray powder diffraction (XRD) clarified that nearly single phase of BaFe12 O19 with tiny traces of Fe2 O3 phase were obtained when the precursor was calcined at 1050 °C for 2 h. The lattice parameters and unit cell volume were almost unchanged with either Cobalt addition or calcination temperatures. From Debye–Scherrer equation, the crystallite size (D) was found to gradually increase with increasing calcination temperature to reach its maximum values for samples calcined at 1050 °C. The formation of Barium hexaferrite phase was also confirmed from Fourier transform infrared (FTIR) spectra through the existence of strong absorption peaks that appeared between 581 cm −1 and 435 cm −1 . The morphology and grain size of the samples were examined using transmission electron microscopy (TEM) technique. Optical properties of the samples were studied through ultraviolet 'UV' visible spectroscopy. The optical band gap (Eg ) of the samples was obtained from Tauc relation as function of Cobalt addition (x) and calcination temperature (T). Finally, the mechanical properties were examined using Vickers microhardness. The microhardness data revealed that the samples exhibited reverse indentation size effect (RISE). The Elastic modulus (E) and yield strength (Y) for the prepared samples were calculated, in accordance with Vickers microhardness, as function of Cobalt addition. Furthermore, the indentation size effect ISE was analyzed using indentation induced cracked model (IIC). The IIC model was found to be a suitable model for describing the microhardness results of the prepared samples. Time dependent Vickers microhardness was done through indentation creep test at different dwell time (t = 10, 20, 30, 40 and 50 s) and constant applied loads (F = 0.98, 4.90 and 9.80 N). Results clarified that the specimens revealed grain boundary sliding together with dislocation climbs at small loads and a dislocation creep in the operating creep process for greater loads.